Multiplicidade narrativa em banda desenhada: a influência dos novos media - Afonso, Joana Isabel Bento da Silva (2019)
This project will focus on how the new media can influence Comics and its language. Thus, presenting a work of both theoretical and practical nature, which looks for answers within the spectrum of the potentialities that a specific narrative can have when adapted to the most varied media. This research is based on theoretical bases, namely on the new paradigms and potential that the new media can offer to Comics. Notions like transmedia and remediation are deepened, since these concepts are essential for the understanding of the context of this project. Transmedia emerge in response to the convergence of new media, and is relative to the creation of worlds, responding to the new demands of readers. This aspect is linked to the notion of remediation, which is the representation of one medium in another. These new concepts are the catalysts for the exploration and analysis present in this project. Such concepts have been explored considering a story created by the author as starting point, which is reinterpreted in four different ways: in a normalized analog format, an analog reduced format, an animated webcomic, and with the use of programming so as to formulate an interactive experience. However, each of these formats had their peculiarities, despite all iterations following the same stylistic and graphical logic, meaning both design and narrative had to be adapted to each one. Here, temporal notions are assessed, in order to verify how the media modified both reading and timing. After completing all the practical components, a comparison was made between excerpts that suffered the most changes from medium to medium, thus analyzing the decision process made for each of them. This investigation is also corroborated by an analytical survey of a set of readers, in order to verify how the changes made in the narrative served the means and ends for which they were chosen, according to each of the formats in which they are inserted. Therefore, this investigation does not end with the verification of which medium is more suitable for the reading of Comics. Moreover, it focuses on establishing the surplus value that each format can offer, depending on the objective of the author upon the transmission of a visual narrative.